Enhancing Classroom Management Through Student Agency In Early Childhood Education (THUFULA, 2025)
This paper explores how student agency relationships take an important role in creating good and effective classroom management, especially when applied in building class agreements through collaborative processes by class members in Early Childhood Education. The background question of this paper is "How can classroom agreements created with student agency contribute to effective classroom management in early childhood education?". Students use their voice and choice in sharing thoughts, making decisions, and allowing them to co-create the rules and expectations that govern their learning environment. Student agency fosters ownership, responsibility and accountability among students through class agreements that adhere to class norms. When students feel like their voices, thoughts, and contributions are valued, they are more likely to internalize classroom agreements and actively participate in maintaining a positive learning environment. This study explores the relationship between student agency and classroom management through classroom agreements using qualitative approach by interview and observation to get pertinent information. It examines how empowering students to take part in setting rules impacts discipline, behavior, emotions, social interactions, and overall classroom dynamics. The results showed that classrooms with student-driven agreements demonstrated higher levels of engagement, reduced behavioral disruptions, more disciplined behavior, and created an active and positive learning environment. The value of student agency is visible in classroom management practices.